Analysis of Covid 19 Vaccination Education on Interest in Implementing Vaccines for Pregnant Women - Erma Retnaningtyas; Retno Palupi Yonni Siwi (Science Midwifery, 2022)
Covid-19 vaccine education program to increase public knowledge and interest, especially pregnant women, considering that pregnant women have a vulnerable immune system and are at high risk of being infected with COVID-19. This research was conducted in Bahomohoni Village, Morowali Regency. The purpose of this study is to analyze the effect of Covid-19 Vaccination Education on the Interest in Implementing Vaccines in Pregnant Women in Bahomohoni Village, Morowali Regency in 2022. This study used a one group pre test post test design. The population in this study amounted to 34 pregnant women. Total sample of 30 respondents used the Accidental Sampling Technique. Data analysis used the Wilcoxon Rank Sum Test. The research instrument used a questionnaire and an extension program unit. Most of the respondents before education had interest in the less category, which was 18 people (60%). The Effect of Covid 19 Vaccination Education on Interest in Implementing Vaccines for Pregnant Women in Bahomohoni Village, Morowali Regency in 2022 with a P-Value of 0.000 There is an Effect of Covid 19 Vaccination Education on Interest in Implementing Vaccines for Pregnant Women in Bahomohoni Village, Morowali Regency in 2022.